Characterization of the Production of Fuels Obtained from the Pyrolysis of Polystyrene - Navarro, Diego; Angulo, Silvana; Castro, Pedro; Salazar, Dany (EASI: Engineering and Applied Sciences in Industry, 2025)
This study addresses the specific characterization of fuels obtained through the pyrolysis of polystyrene after being analyzed in laboratories and a study of their applicability. Pyrolysis is the chemical decomposition of materials by heating them at high temperatures without the presence of oxygen to decompose them into simpler fractions. The research focused on evaluating viscosity, flash point, density and ASTM distillation and then comparing the results with commercial fuel standards. The results show that pyrolysis-derived fuels have characteristics intermediate between diesel and gasoline, with a density similar to diesel, but a viscosity and flash point closer to gasoline. Distillation reveals a mixture of volatile and non-volatile components, suggesting that these fuels could be alternatives, although further testing to evaluate their performance and safety in specific applications is needed to validate the feasibility and safety of polystyrene pyrolysis by-products as alternative fuels.